Analisis Faktor-Faktor yang Mempengaruhi Meningkatnya Pertumbuhan Ekonomi Singapura - Ahmad Ghazy Al Mubarok; Dinda Amalia Putri C; Nika Santika; Citra Sukma Dewi Br Saragi (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study aims to identify and analyze the factors that influence economic growth in Singapore. The research method used is a qualitative method with descriptive analysis techniques using a literature review approach such as scientific journals and digital books. The results showed that the factors that influence the increase in Singapore's economic growth are foreign direct investment, progressive economic policies, export sector and international trade, energy consumption and infrastructure, human resources and education, finance and banking sector, innovation and technology and strategic geographical location and research issues discussed.